PERTUMBUHAN Lactobacillus casei subsp. rhamnosus PADA MEDIA YANG DISUPLEMENTASI TEPUNG KOLANG-KALING - Widedianto, I Nengah; Antara, Nyoman Semadi; Wijaya, I Made Mahaputra (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2017)
Sugar palm (Arenga pinnata) is a plant that produces industrial materials. Almost all parts or products of these plants can be utilized and have economic value. One product can by be produced sugar palm is a fruit that can be processed into sugar palm fruit. The components contained in the sugar palm fruit especilly galactomanan, are expected to enhance the growth of the microflora in the digestive tract including lactic acid bacteria (LAB). This study was aimed to determine the concentration of sugar palm fruit flour in stimulating the growth of lactic acid bacteria (Lactobacillus casei subsp. rhamnosus) . In vitro experiments conducted in the laboratory with treatment of sugar palm fruit flour with glucose as a control. Medium used was yeast-peptone medium supplemented with 1% glucose, 0% sugar palm fruit flour, 0.5% sugar palm fruit flour, 1% sugar palm fruit flour, 1.5% sugar palm fruit flour, and 2% sugar palm fruit flour. Fermentation was carried out at 37 °C for 9 hours. The results showed that during the fermentation was occured the growth of the bacteria followed by the change of pH and total acids that strengthen the research results. The best concentration of sugar palm fruit flour that the highest stimulating effect on the growth of Lactobacillus casei subsp. rhamnosus was 1.5%. [Keywords]: Sugar palm, sugar palm fruit, Lactobacillus casei .
Keywords: 136